DEVELOPMENT OF HISTORICAL FERGANA CITY CENTERS - Muminova , Nigoraxon Zokhidovna (Educational Research in Universal Sciences, 2024)
In this article, the main task of reconstructing the historical city center should be to adapt the positive qualities of the historically established urban complex to the vital needs and amenities of modern society.